The many faces of social media in business and economics research: Taking stock of the literature and looking into the future - Andranik Tumasjan (Journal of Economic Surveys, 2023)
Since their inception more than 15 years ago, social media have become a vibrant research topic in business and economics research. This article presents an integrative literature review taking stock of and showing the many faces of social media in extant research. Based on N = 1419 articles published in the leading peer-reviewed business and economics journals in the years 2008–2022, we identify and describe seven overarching research themes, namely, social media as a: (1) market-oriented interaction hub, (2) resource-oriented interaction hub, (3) information market, (4) innovation and business venturing hub, (5) societal challenge, (6) political hub, and (7) data source. Finally, we derive a research agenda to stimulate future research on this increasingly important topic.
Keywords: 330; social media; social network; social networking; Facebook; Twitter; Weibo